Energy-efficient SO2OR-coupled CO2 electroreduction for concurrent formate synthesis and sulfur recovery - Haoyu Cheng; Yaobin Wang; Chaoyue Xie; Hang Yang; Changhui Zhou; Yongyang Chen; Jinhua Li; Jing Bai; Baoxue Zhou (Journal of Environmental Chemical Engineering, 2026)

Enhanced photo-fermentative hydrogen production in photosynthetic bacteria via nano-Fe3O4-improved photosynthetic electron transfer efficiency - Cheng Sun; Jianpeng Wang; Qilin Yu; Zhiqiang Zhao; Yaobin Zhang (Environmental Research, 2025)

Identification of Aggregation Pheromone as an Attractant for Odontothrips loti, A Serious Thrips Pest on Alfalfa - Xiaowei Li; Jianghui Cheng; Haibin Han; William D.J. Kirk; Matthew O’Brien; Likun Wang; Limin Chen; Haixia Zhang; Zhijun Zhang; Farman Ullah; Nicolas Desneux; Yaobin Lu (Journal of Chemical Ecology, 2024)
Odontothrips loti (Haliday) (Thysanoptera: Thripidae) is one of the most serious pests on alfalfa, causing direct damage by feeding and indirect damage by transmitting plant viruses. This damage causes significant loss in alfalfa production. Semiochemicals offer opportunities to develop new approaches to thrips management. In this study, behavioral responses of female and male adults of O. loti to headspace volatiles from live female and male conspecifics were tested in a Y-tube olfactometer. The results showed that both male and female adults of O. loti were attracted to the odors released by conspecific males but not those released by females. Headspace volatiles released by female and male adults were collected using headspace solid-phase microextraction (HS-SPME). The active compound in the volatiles was identified by gas chromatography-mass spectrometry (GC-MS). The analysis showed that there was one major compound, ( R )-lavandulyl ( R )-2-methylbutanoate. The attractive activity of the synthetic aggregation pheromone compound was tested under laboratory and field conditions. In an olfactometer, both male and female adults showed significant preference for synthetic ( R )-lavandulyl ( R )-2-methylbutanoate at certain doses. Lures with synthetic ( R )-lavandulyl ( R )-2-methylbutanoate significantly increased the trap catches of sticky white traps at doses of 40–80 µg in the field. This study confirmed the production of aggregation pheromone by O. loti male adults and identified its active compound as ( R )-lavandulyl ( R )-2-methylbutanoate, providing a basis for population monitoring and mass trapping of this pest.

Strengthening the cathodic CO2 adsorption on the MIL-88B(Fe) to enhance methane production - Zhihao Jiang; Yue Ding; Zhiqiang Zhao; Qilin Yu; Cheng Sun; Yaobin Zhang (Chemical Engineering Journal, 2024)

Effects of electrical stimulation on carbon sequestration of photosynthetic bacteria: Response of the photosynthetic unit to electrical stimulation - Cheng Sun; Qilin Yu; Zhiqiang Zhao; Yaobin Zhang (Journal of Cleaner Production, 2024)

New insights into inhibition of high Fe(III) content on anaerobic digestion of waste-activated sludge - Xuepeng Wang; Yijing Gong; Cheng Sun; Zhenxin Wang; Ye Sun; Qilin Yu; Yaobin Zhang (Science of The Total Environment, 2024)

Focus on Co-digestion of waste activated sludge and food waste via yeast pre-fermentation and biochar supplementation: The optimization and mechanism - Yahui Zhu; Cheng Sun; Yaobin Zhang (Environmental Research, 2023)

Enhancing photosynthetic CO2 fixation in microbial electrolysis cell (MEC)-based anaerobic digestion for the in-situ biogas upgrading - Cheng Sun; Qilin Yu; Zhiqiang Zhao; Yaobin Zhang (Chemical Engineering Journal, 2023)

Fertilizer N triggers native soil N-derived N2O emissions by priming gross N mineralization - Cong Xu; Hanshen Zhu; Jing Wang; Cheng Ji; Yaobin Liu; Danyan Chen; Hui Zhang; Jidong Wang; Yongchun Zhang (Soil Biology and Biochemistry, 2023)

High-level expression of a novel recombinant human plasminogen activator (rhPA) in the milk of transgenic rabbits and its thrombolytic bioactivity in vitro - Shaozheng Song; Xin Ge; Yaobin Cheng; Rui Lu; Ting Zhang; Baoli Yu; Xueqiao Ji; Zhengqiang Qi; Yao Rong; Yuguo Yuan; Yong Cheng (Molecular Biology Reports, 2016)

China’s wetland change (1990–2000) determined by remote sensing - Peng Gong; ZhenGuo Niu; Xiao Cheng; KuiYi Zhao; DeMin Zhou; JianHong Guo; Lu Liang; XiaoFeng Wang; DanDan Li; HuaBing Huang; Yi Wang; Kun Wang; et al. (Science China Earth Sciences, 2010)